A report on the wetland avifauna of South Sulawesi - Michael C Baltzer (KUKILA, 1990)
The bird communities of the wetlands in South Sulawesi are discussed from results and observations made from an ecological survey undertaken over seven months in the province. The present status of the surveyed wetland habitats is listed. The bird communities observed in these wetlands are then reported and discussed. Annotations are made on selected species. Results from frequent surveys In the Tempe lake system indicate it to be a wetland habitat of international importance according to the Ramsar Convention, mainly because of large concentrations of birds including 10,000+ Garganey . 5,000 Glossy Ibis and 26,000 Great/Clamorous Reed-Warbler. New distribution recordings are made for the Maleo, the Woolly-necked Stork and the Grey-headed Fish-Eagle. Threats to the bird populations are discussed which include threats from pesticide use, live bird trading, hunting and loss of habitat.